Ultrasound Guidance for Technically Challenging Intrathecal Baclofen Pump Refill: Three Cases and Procedure Description. (September 2016) - Maneyapanda, Mithra B.; Chang Chien, George C.; Mattie, Ryan; Amorapanth, Prin; Reger, Christopher; McCormick, Zachary L.
Abstract : ABSTRACT: Intrathecal baclofen (ITB) therapy is a common treatment used to reduce spasticity due to neurologic disorders and injuries. A variety of factors can increase the difficulty of ITB pump refill. Excess subcutaneous fat overlying the pump, spasticity, suboptimal positioning, pump rotation or inversion, and scar formation over the reservoir fill port can create challenges during pump refill. As a result, multiple unsuccessful attempts at accessing the reservoir fill port can be painful and increase the risk of infection, particularly when repeat skin puncture is required. Blind attempts to refill a pump in challenging cases may also result in subcutaneous injection or pocket fill, resulting in a potentially fatal baclofen withdrawal syndrome. We describe 3 successful ITB pump refills in technically challenging cases when using ultrasound guidance. This represents an innovative approach to using ultrasound guidance to facilitate ITB refill in adults with intractable spasticity. We present these new clinical data with a literature review of potential complications related to inaccurate pump refill procedures and discuss the utility of ultrasound guidance for preventing such adverse events.